Reverse micelle-lipid nanocapsules: a novel strategy for drug delivery of the plectasin derivate AP138 antimicrobial peptide - Groo AC (Dove Medical Press, 2018)
Anne-Claire Groo,1 Nada Matougui,2 Anita Umerska,2,3 Patrick Saulnier2,4 1Normandie Univ, UNICAEN, CERMN - EA 4258, FR CNRS 3038 INC3M, SF 4206 ICORE, Caen, France; 2Micro & Nanomédecines Translationelles-MINT, UNIV Angers, INSERM U1066, CNRS UMR 6021, UBL Universite Bretagne Loire, Angers, France; 3Université de Lorraine, CITHEFOR, Nancy, France; 4Angers University Hospital, Angers, France Introduction: Resistance to traditional antibiotics is an increasingly serious problem. Antimicrobial peptides (AMPs) have emerged as a new therapeutic class with great potential against infectious diseases, as they are less prone to induce resistance. Nanotechnology-based delivery strategies can improve the efficiency and stability of AMPs, particularly against proteolytic degradation. Lipid nanocapsules (LNCs) are a new generation of biomimetic nanocarriers and were used in this study to deliver peptides.Methods: AMP-loaded reverse micelles (RM) were developed and incorporated into LNCs by the phase inversion process and the antimicrobial activity of the AMPs-loaded LNC was evaluated by the minimum inhibitory concentration method. We studied the activity of AMP solutions and AMP-loaded LNCs against Gram-positive and Gram-negative bacterial strains and then evaluated the encapsulation of a new cationic AMP called AP138. Finally, we analyzed the effect of enzymatic attack on AP138 and AP138-RM-LNCs after incubation with trypsin.Results: AP138 was efficiently encapsulated in the LNCs (encapsulation efficiency = 97.8% at a drug loading of 0.151%), resulting in protection against degradation by proteases and the preservation of antimicrobial activity against Staphylococcus aureus, including methicillin-resistant Staphylococcus aureus.Conclusion: This study shows that RM-LNCs are an excellent candidate system to deliver AMPs. Keywords: nanoparticles, nanomedicine, antibacterial, AMP, methicillin-resistant Staphylococcus aureus, infection